2021
DOI: 10.1186/s13075-021-02447-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of a model for predicting the 4-year risk of symptomatic knee osteoarthritis in China: a longitudinal cohort study

Abstract: Objectives We aimed to develop a model for predicting the 4-year risk of knee osteoarthritis (KOA) based on survey data obtained via a random, nationwide sample of Chinese individuals. Methods Data was analyzed from 8193 middle-aged and older adults included in the China Health and Retirement Longitudinal Study (CHARLS). The incident of symptomatic KOA was defined as participants who were free of symptomatic KOA at baseline (CHARLS2011) and diagnos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 52 publications
3
20
0
Order By: Relevance
“…Previous studies have defined disability as an inability to perform ADL or IADL, and found that older adults with chronic conditions and women are at a higher risk of developing a disability 36 , 37 . Older adults living in rural areas have limited access to knowledge regarding the prevention and timely treatment of chronic diseases; a lack of economic resources; and earlier impairments in physical function due to strenuous farm work 38 . It is a well-known that chronic diseases are strongly associated with functional decline.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have defined disability as an inability to perform ADL or IADL, and found that older adults with chronic conditions and women are at a higher risk of developing a disability 36 , 37 . Older adults living in rural areas have limited access to knowledge regarding the prevention and timely treatment of chronic diseases; a lack of economic resources; and earlier impairments in physical function due to strenuous farm work 38 . It is a well-known that chronic diseases are strongly associated with functional decline.…”
Section: Discussionmentioning
confidence: 99%
“…Symptomatic KOA was defined as both doctor-diagnosed arthritis and self-reported pain in the knee joint. The presence of knee joint pain was assessed based on the following question: “Are you often troubled by pain in any part of your body?” and “In what part of your body do you feel pain?” [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…They found that patients with mild or moderate to severe depression had a two- or three-times higher risk of developing KOA than those without depression. 30 The risk model showed good discrimination with area under the receiver operating characteristic curve (AUC) = 0.719 (95% CI = 0.700–0.737) and optimism-corrected AUC = 0.712 after bootstrap validation. Similar studies are rare; thus, there is a lack of robust data to support such a hypothesis.…”
Section: Depression and Oa: Epidemiological Associationmentioning
confidence: 96%
“…Recently, Wang et al developed a symptomatic KOA prediction model using secondary analysis of the China Health and Retirement Longitudinal Study data to identify individuals at risk of developing KOA. 30 The authors concluded that previous KOA prediction models had ignored many potential predictors; therefore, this study included depressive symptoms variables in the model. They found that patients with mild or moderate to severe depression had a two- or three-times higher risk of developing KOA than those without depression.…”
Section: Depression and Oa: Epidemiological Associationmentioning
confidence: 99%